"An In-Vitro Approach to Identifying Potential Drug Candidates to Prevent Acetaminophen Toxicity" - Youngblood, Vaughn. (2017)
Abstract: Abstract Hepatic toxicity due to acetaminophen (APAP) is the leading cause of acute liver failure in the United States. Acetaminophen is largely metabolized by sulfotransferases and glucuronyl transferases. Once these enzymes are saturated, APAP is metabolized by CYP450 enzymes, particularly CYP2E1, into a hepatotoxic metabolite called N-acetyl- ρ-benzoquinone imine (NAPQI). Quantitatively measuring the accumulation of this toxic metabolite has been an elusive topic in previous literature. The analysis of the complex that NAPQI forms with hepatic glutathione (NAPQI-GSH) is the most reliable approach to quantitate metabolite formation. Using HPLC, incubations of increasing concentrations of APAP using human liver microsomes were performed in order to quantify toxic metabolite. To determine if the NADPH-regenerating system within the reaction was functioning as expected, incubations with midazolam, a benzodiazepine which undergoes CYP450 metabolism to hydroxylated metabolites, were performed Concentrations of 2 μM, 5 μM, 20 μM, 50 μM, 200 μM, 500 μM, and 1mM APAP were used for incubations. Incubations consisted of NADPH-regenerating system including NADP+, MgCl2, sodium citrate, glucose-6-phosphate (G6P), and G6P dehydrogenase. Phosphate buffer and 1mM APAP (stock) were used as standards. Mobile phase consisted of 80% potassium phosphate (pH 2.2) and 20% methanol. A reverse-phase C18 column was used to process the reactions (Waters Nova-Pak® C18 (4μm; 3.9x150mm)). UV absorbance was measured at 254nm. Midazolam incubations were performed using a Waters Nova-Pak® C18 (4μm; 3.9x150mm) HPLC column. The NAPQI-GSH metabolite peak was not able to be clearly defined with the specified method. HPLC analysis of APAP incubations yielded no significant metabolite peak formation. Further investigation using a similar HPLC method is needed.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Pharmacology & Experimental Therapeutics.; Advisors: David Greenblatt, and Margery Beinfeld.; Keyword: Pharmacology.